Identifikasi dan Keragaman Genetik Longtail Tuna (Thunnus tonggol) Yang Didaratkan di PPI Kedonganan dan PPP Muncar Menggunakan Marka D-loop Mitokondria - Enex Yuniarti Ningsih; Elok Faiqoh; Ida Ayu Astarini; Putu Dian Pertiwi; Andrianus Sembiring; Ni Luh Astria Yusmalinda; Muhammad Danie Al Malik (Fakultas Kelautan dan Perikanan Universitas Udayana, 2021)
Longtail tuna (Thunnus tonggol) is one of the oceanodromus neritic species and the migration pattern follows the water currents. Currently, this species has not been widely studied in Indonesian waters, so it is nesessary to study the identification of morphology and genetic diversity. The molecular approach employed in this study is DNA barcoding using mitochondrial D – loop locus. This study can explain the importance of species genetic information in stability and resilience. This study aims to determine the identification of morphology, phylogenetic and genetic diversity of longtail tuna at two locations in PPI Kedonganan, Bali dan PPP Muncar, Banyuwangi. The molecular analysis was done in several stages, i.e DNA extraction, Polymerase Chain Reaction, electrophoresis and sequencing. Based on the result of sequencing and analysis, 33 samples of longtail tuna was found. The result of phylogenetic tree reconstruction from two locations showed one clade with genetic distance value among longtail tuna species ranging from 0.000 – 0.042 for all close kinship samples. The haplotype diversity (Hd) value of longtail tuna was 0.9905 and nucleotide diversity (?) was 0.020. The high value of genetic diversity indicated that two longtail tuna populations have a high survival ability to adapt on environmental changes. Index fixation analysis (Fst) has a value of 0.0299, p - value > 0.05. The index fixation value indicated no significant population difference. The result of this study can be use as basic data in planning genetic conservation strategies with sustainable fisheries management efforts. Keywords: Tuna; Thunnus tonggol; Genetic Marker